2018
DOI: 10.1088/1742-6596/1003/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of porous silicon gas sensors

Abstract: Abstract. In this work, photo-electrochemical etching process of n-type Silicon of resistivity(10 Ω.cm) and (100) orientation , using two illumination sources IR and violet wavelength in HF acid have been used to produce PSi gas detection device. The fabrication process was carried out at a fixed etching current density of 25mA/cm2and at different etching time (5, 10, 15 and 20) min and (8, 16, 24, and 30) min. Two configurations of gas sensor configuration planer and sandwich have been made and investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The amount of porosity of the samples prepared in this way depends on several parameters, the most important of which are the concentration of the solution, the current density, the etching time, and the intensity of the laser beam applied to the sample [11][12][13]. The influence of laser beam intensity on the amount of porosity and pore diameter of the sample prepared from n-type silicon has been studied in this work, as has the latter's effect on the amount of sensitivity, which has been discussed with the usage of methanol gas [14,15]. When used as a sensor for environmental pollution with toxic gases, the PSi was prepared and studied to determine the effect of the preparation conditions on its properties [16,17].…”
Section: Theoretical Partmentioning
confidence: 99%
“…The amount of porosity of the samples prepared in this way depends on several parameters, the most important of which are the concentration of the solution, the current density, the etching time, and the intensity of the laser beam applied to the sample [11][12][13]. The influence of laser beam intensity on the amount of porosity and pore diameter of the sample prepared from n-type silicon has been studied in this work, as has the latter's effect on the amount of sensitivity, which has been discussed with the usage of methanol gas [14,15]. When used as a sensor for environmental pollution with toxic gases, the PSi was prepared and studied to determine the effect of the preparation conditions on its properties [16,17].…”
Section: Theoretical Partmentioning
confidence: 99%
“…These properties of (PSi), such as pore form, pore width, and the wall thickness between adjacent pores, have been examined using a scanning electron microscope to create a clear picture of the structure (SEM) [10]. The SEM images of the PS layers cantered on the c-Si n-type (100) wafer with etching time at 30, 60, and 90 min respectively, and current density (20mA/cm 2 ) at magnification 50.0kx.…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…The results showed more pores found with larger sizes and a decrease in the thickness of the walls between the pores with an increase in the etching time. The increase in the etching time improves the degradation process of silicon crystals, which causes the generation of more electron-hole pairs [10]. The luminous region indicates the structure of the silicon, and the darker region indicates the porous silicon formed.…”
Section: Morphological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with the above-mentioned optical transducers, nano-Si is widely used for (bio)sensor application based on electrical and electrochemical responses [77]. For instance, I(J)-V measurements were carried out for the detection of biomolecules [79,105], gases [21,49,106,107,108], light [109,110,111], and pH [112,113,114]. Shashaani et al reported about Mebendazole (MBZ) drug activity on breast cancer cells (MCF-7) adhered over a SiNW chip [105].…”
Section: (Bio)sensors Based On Psi Sinws Sinps and Their Composimentioning
confidence: 99%